2019
DOI: 10.1073/pnas.1905558116
|View full text |Cite
|
Sign up to set email alerts
|

Structures of the cGMP-dependent protein kinase in malaria parasites reveal a unique structural relay mechanism for activation

Abstract: The cyclic guanosine-3′,5′-monophosphate (cGMP)-dependent protein kinase (PKG) was identified >25 y ago; however, efforts to obtain a structure of the entire PKG enzyme or catalytic domain from any species have failed. In malaria parasites, cooperative activation of PKG triggers crucial developmental transitions throughout the complex life cycle. We have determined the cGMP-free crystallographic structures of PKG fromPlasmodium falciparumandPlasmodium vivax, revealing how key structural components, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(88 citation statements)
references
References 54 publications
7
74
0
Order By: Relevance
“…Further data showed that CNB-A and -B modulated kinase activity whereas CNB-C had no obvious function. Additional crystallographic data confirming these results and revealing further information on the regulation of PKG activation by AIS and the different CBDs have just been published (El Bakkouri et al 2019).…”
Section: The Role Of Cgmp For Infectious Diseasessupporting
confidence: 58%
“…Further data showed that CNB-A and -B modulated kinase activity whereas CNB-C had no obvious function. Additional crystallographic data confirming these results and revealing further information on the regulation of PKG activation by AIS and the different CBDs have just been published (El Bakkouri et al 2019).…”
Section: The Role Of Cgmp For Infectious Diseasessupporting
confidence: 58%
“…To simplify the analysis, we focused on the C-terminal helices that are directly linked to the catalytic domain and are one of the allosteric elements most critical in the inhibition and activation of the kinase (14,21,24). The C-terminal helices span two regions with clearly distinct average X values (<X>) in the PfD:8-NBD-cGMP complex: residues 515-530, denoted as the pre-lid with <X> = -0.48, and residues 534-535, denoted as the lid with <X> = -0.88 ( Fig.…”
Section: The Chemical Shift Projection Analyses (Chespa) Of the Cgmp-mentioning
confidence: 99%
“…The structure of 8-NBD-cGMP in a syn conformation was generated using RDKit (47). A model of the mixed intermediate state sampled by the PfD:8-NBD-cGMP complex was then built using residues 401-533 from the active PfD:cGMP crystal structure (PDB code: 4OFG) (14), and lid region residues 534-542 from the inactive apo PfD crystal structure (PDB code: 5DYK) (24). The 8-NBD-cGMP ligand was docked into the resulting mixed structure of PfD using AutoDock4 with default parameters generated by AutoDockTools (48).…”
Section: Molecular Dynamic Simulations Initial Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, PKG inhibitors have the potential to be active against multiple malaria species. Although human PKG orthologues (cytosolic PKG-Iα and PKG-Iβ, membrane-associated PKG-II) exist, selective inhibitor development is still possible as there is significant structural divergence between plasmodial and mammalian PKGs [74].…”
Section: Inhibitor Development For the Agc Groupmentioning
confidence: 99%